Modeling and experimentation for novel aerofoil embedded mesh disk-based partially submerged rotating reactor - Sunil K Saini (Chemical Engineering Journal Advances, 2022)
A novel aerofoil embedded fiber mesh disk-based rotor has been proposed as an alternative to currently available rotating biological contactors. Specially designed aerofoil structures were incorporated into the rotor to increase its mass transfer performance and liquid hold capacity. The volumetric mass transfer coefficient and liquid hold-up for the novel rotor were determined at the rotational speeds of around 10, 15, 20, 25, 30, and 35 rpm under various submergence levels of 17.4, 21.7, 26.1, 27.8, 30.4, 34.8, 39.1, 43.5, and 50%. A dimensionless correlation for the dynamic liquid hold-up was proposed in terms of the Reynolds number, Froude number, and the submergence ratio. Another dimensionless term Oxygen transfer number (OT number) was proposed to characterize the mass transfer behavior of the reactor. The dependency of OT number was expressed in terms of Peclet number, Froude number, and dimensionless geometrical factor. The volumetric mass transfer coefficient and liquid hold-up were found to be strongly dependent on the rotation speed and submergence level.